COPING STRATEGIES BY STROKE CAREGIVERS: EVIDENCE FROM A QUALITATIVE STUDY IN SARAWAK, MALAYSIA - Md Mizanur Rahman; Zabidah binti Putit; Norliza binti Suut; Mohamad Taha Arif; Asri bin Said; Mohd Raili bin Suhaili; Mohd Fadzillah; Zainab binti Tambi; Ling How Kee (Malaysian Journal of Public Health Medicine, 2020)
Caring for stroke survivors is inevitably a burden to caregivers. It is not uncommon for stroke survivors who are discharged from the hospital and found themselves at home without any help and care from the supposed caregivers. However, in instances where there are available and willing caregivers, a sudden and unpredictable task of caring for stroke survivors require the stroke caregivers to apply their coping strategies due to the demanding nature of looking after a survivor. This study aimed to determine coping strategies undertaken by stroke caregivers in caring for stroke survivors. This was an exploratory qualitative study and data was collected from the caregivers of stroke survivor using a semi-structured guided questionnaire. A total of 18 caregivers were included in the study. The data were collected from November 2015 until June 2016 at a selected community rehabilitation centre in Kuching, Sarawak. The qualitative data analysis revealed that the coping strategies undertaken by stroke caregivers include change of role in life, self-motivation, sharing with other people, crying, trying to forget things that happen, hoping survivors will get better, emotion suppression and self-blame. The study highlighted the experiences by the caregivers for caring for stroke patients and focused on the coping strategies undertaken by the caregivers. Better ununderstanding of these experiences does help the service providers to provide better support and resources for caregivers in caring for stroke survivors.